Alternating direction method for two-dimensional parabolic equation with nonlocal integral condition - Sapagovas, Mifodijus; Jakubėlienė, Kristina (Nonlinear Analysis: Modelling and Control, 2012)
Two-dimensional parabolic equation with nonlocal condition is solved by alternating direction method in the rectangular domain. Values of the solution on the boundary points are bind with the integral of the solution in whole two-dimensional domain. Because of this nonlocal condition, the classical alternating direction method is complemented by the solution of low dimension system of algebraic equations. The peculiarities of the method are considered.